Evaluation of methods for stain removal in acrylic resin denture teeth: in vitro study - Ana Flávia Balestrero CASSIANO; Andressa Rosa Perin LEITE; Vivian Barnabé POLICASTRO; Marco Antonio COMPAGNONI; Ana Carolina PERO
Abstract Introduction The staining of artificial teeth can be related to the acrylic resin abrasion caused by brushing, resulting in higher deposition of dyes from the beverage, and consequently higher aesthetic damage. Objective The aim of this in vitro study was to evaluate methods for removal of stains from acrylic denture teeth using spectrophotometric analysis. Material and method Artificial teeth were divided into twelve groups (n=10) according to the type of treatment (re-polishing - Re or immersion in Corega Tabs - Sp), staining solutions, coffee (Cf) and Coca-Cola® (Cc) or water (W) and with/without toothbrushing (B). The Sp specimens were submitted to seven immersion cycles (5 min each). The Re specimens were polished with pumice stone followed by Spain white paste. Color differences (ΔE) were captured by a spectrophotometer: T0 (baseline), T1 (after brushing/immersion in solutions) and T2 (after Re or Sp). Result Statistically significant color change between T1 and T2 (paired T-test; α =.05) was observed for the group CfSp (p=.032); and for the groups BWRe (p=.000), BCfRe (p=.049) and CcRe (p=.042). Higher color changes were observed for the specimens submitted to toothbrushing (ANOVA two way; p<.001). Conclusion It could be concluded that the immersion in sodium perborate (Corega Tabs) can be used for removal of coffee stains from denture teeth, and re-polishing for removal of Coca-Cola® stains. Still, toothbrushing produced greater color changes on denture teeth, regardless of the immersion solution.